Promoting mammography screening among Chinese American women using a message-framing intervention. Issue 7 (July 2015) - Sun, Yiyuan; Sarma, Elizabeth A.; Moyer, Anne; Messina, Catherine R.
Highlights Chinese American women are underrepresented in mammography screening intervention research. We evaluated a culturally targeted message framing intervention to increase mammography. Framed messages matched to decisional balance significantly improved screening rates.